Analysis Of Hospital Assistant Behavior On Medical Waste Handling System In HVA Pare Hospital - Cahyono M. Wijanarko, Dwi; Nurdina; Rusmawati, Aprin (Journal of Global Research in Public Health, 2019)
Improper handling of medical waste, the janitor as the manager must have behavior in accordance with applicable medical waste processing standards. It is necessary to know what factors cause the behavior of janitors not yet according to existing standards. The purpose of this study was to determine the effect of Hospital Officers' Behavior on medical waste handling systems in HVA Hospital Pare. The design of this study is observation / survey with a cross-sectional approach. The sampling technique is purposive sampling. The sample in this study were 53 people. Independent variables were the behavior of officers and the dependent variable was medical waste handling. The statistical test is linear regression. The results showed good behavior as many as 32 respondents (60.4%) of a total of 53 respondents, medical treatment of medical waste was as much as 30 respondents (56.6%) out of a total of 53 respondents. The results of the analysis showed that there was an influence of the Behavior of Cleaning Officers on the Medical Waste Treatment System in HVA Pare Hospital with a significant value = 0.002 <0.05 Handling medical waste in hospitals HVA is influenced by good behavior to improve the comfort of the hospital environment. Clean hospitals can deal with medical waste that is correct in accordance with existing SOPs so as not to contract infectious diseases from medical objects that have been used